IMPACT OF BIOMEDICAL SENSORS IN HEALTHCARE MONITORING - Abdulaziz Owaiydh Najr Alrakhimi,Fahad Abdulrazeq Aljuwaie ,Sami Mana K Alanazi,Saad Naji Aldawsari,Omar Salem Aldosari,Osamah Zaid Jazaa Almutairi,Bander Abdullatif Alghamdi,,; Abdullah Fahad Abdulaziz Alsuliman,Bader Nasser Abdulaziz Alhamidi,Adel Lafi Al Otaibi,Ahmed Saad Ahmed Okailan,Mohammad Ali Yahya Asiri,Abdulrahman Ibrahim Almutrad, (Chelonian Research Foundation, 2022)
An investigation was conducted on the latest advancements in wearable flexible sensors (WFSs) designed for the detection of sweat analytes. Recent progress has shown the creation of sensor systems that are integrated, mechanically flexible, and capable of multiplexing. These systems also include on-site electronics for signal processing and wireless data transfer. Compared to sensors that just measure one substance, these devices provide a chance to analyze substances that are influenced by other factors (such sweat rate and pH) with more accuracy. This is achieved by enhancing the calibration process via real-time analysis in the actual environment, all while keeping the device lightweight and easy to wear. Integrated wearable devices can monitor important health parameters and distribute medications as needed. However, before these systems can be used in clinical applications, it is necessary to verify the connection between sweat and blood readings via in vivo validation testing. Enhancements are required to enhance the sensitivity, precision, and consistency of the device in order to provide more dependable and customized continuous measurements. Recent advancements in non-invasive wearable biosensors for sweat analysis have merely scratched the surface of their potential for health monitoring. Further considerable progress is expected to be achieved in the medical area.